2020
DOI: 10.11604/pamj.2020.36.76.21511
|View full text |Cite
|
Sign up to set email alerts
|

Influence des comorbidités sur l´évolution et le pronostic des patients porteurs de broncho-pneumopathie chronique obstructive dans un centre tunisien

Abstract: Introduction la broncho-pneumopathie chronique obstructive (BPCO) s’associe fréquemment avec des comorbidités. L’objectif de notre travail est d'étudier l'impact des comorbidités sur l’évolution et le pronostic de la BPCO. Méthodes il s’agit d’une étude rétrospective incluant des patients porteurs de BPCO hospitalisés et/ou suivis à la consultation de Pneumologie au Centre Hospitalo-Universitaire Fattouma Bourguiba de Monastir entre Janvier 2000 jusqu’à Décembre 2017. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…An observational study of the valuation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE) concluded that the prevalence of comorbidities is higher in COPD patients, reaching up to 38%, compared to smokers with normal lung function and non-smokers [ 35 ]. In addition, a recent study conducted on COPD patients in a Tunisian Hospital established that comorbidities in COPD patients result in poorer prognosis and higher severity of symptoms [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study of the valuation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE) concluded that the prevalence of comorbidities is higher in COPD patients, reaching up to 38%, compared to smokers with normal lung function and non-smokers [ 35 ]. In addition, a recent study conducted on COPD patients in a Tunisian Hospital established that comorbidities in COPD patients result in poorer prognosis and higher severity of symptoms [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, many confounding factors also play a role in the pathophysiology of anemia in COPD patients like cardiovascular disorders, old age, malnutrition, occult blood loss, drugs such as angiotensin-converting enzyme inhibitors or theophylline, endocrine abnormality, and oxygen therapy [36,[44][45][46]. Therefore, screening for other types of anemias, such as iron, folate, or vitamin B12 deficiency, is also necessary for COPD patients [36,45].…”
Section: Copd and Anemiamentioning
confidence: 99%